Penggunaan Hormon Tumbuh Alami dan Komposisi Media Tanam Terhadap Pertumbuhan Bibit Kakao - Ramanda, Rika Fitry; Palupi, Tantri; Rianto, Fadjar (Politeknik Negeri Lampung, 2024)
Cocoa seeds are recalcitrant seeds, namely seeds that cannot tolerate drying, and are sensitive to low temperatures and humidity. Naturally, cocoa seeds do not have dormancy, have low shelf life and are sensitive to changes in the storage environment. Therefore, proper handling is required after the seeds arrive at their shipping destination (after the seeds have been stored during shipping). Among them is by providing growth regulator (ZPT) treatment, so that seed vigor can be maintained. Cocoa plants can grow well if planted in media with a composition of organic materials and nutrients needed by the plants. This research aims to look at the interaction of natural growth hormones and planting media on cocoa seeds which experience a decrease in quality on the growth of cocoa seedlings. This research used a split plot design with a RAL pattern consisting of a main plot which was a combination of planting media and sub plots which were natural growth hormones, each treatment was repeated 3 times. Each experimental unit consisted of 3 seed samples, so that 90 seeds were obtained. The research results showed that there was no interaction between the use of natural growth hormones and the composition of the planting medium on the parameters of seed water content, vigor index, germination power, growth speed, seed height, number of leaves, leaf area and root volume, as well as seed dry weight. The best hormonal treatment for the parameters of leaf area, root volume and dry weight of seedlings is a hormone from tomato extract. The best planting media composition is alluvial topsoil + chicken manure + husk charcoal (1 : 1 : 1).